Etanercept decreases synovial expression of tumour necrosis factor-α and lymphotoxin-α in rheumatoid arthritis. (March 2014) - Neregård, P; Krishnamurthy, A; Revu, S; Engström, M; af Klint, E; Catrina, AI
<x xml:space="preserve">Abstract</x> Objectives: Etanercept is an effective tumour necrosis factor (TNF)-α inhibitor drug with the unique ability to block not only TNF-α but also lymphotoxin (LT)-α, at least in vitro. We aimed to investigate the in vivo effect of etanercept on synovial expression of TNF-α and LT-α. Method: Synovial biopsies from 12 rheumatoid arthritis (RA) patients started on etanercept and 11 RA patients started on infliximab were obtained at baseline and 8 weeks after treatment initiation. Synovial expression of TNF-α and LT-α was evaluated by immunohistochemistry followed by computer-assisted image analysis. Differences between paired samples were analysed by the Wilcoxon test and between groups by the Mann–Whitney test. A p-value < 0.05 was considered statistically significant. Results: Six out of the 12 of the patients started on etanercept achieved an American College of Rheumatology (ACR)50 response. Macroscopic evaluation of the joints during arthroscopy revealed a significant decrease of local inflammation mainly in good ACR50 responders. Synovial expression of both LT-α and TNF-α decreased but the differences did not reach statistical significance at a group level. By contrast, a significant decrease in both LT-α and TNF-α was observed when only good ACR50 responders were analysed. Despite higher levels of baseline synovial TNF-α in the good responders, neither baseline LT-α nor TNF-α could predict clinical response after 8 weeks. A decreasing trend of the synovial levels of LT-α was also observed in good responders to infliximab, but the difference did not reach statistical significance. Conclusions: Etanercept treatment modulates the synovial expression of both TNF-α and LT-α in vivo, a mechanism that might partly explain its clinical efficacy in RA.